Supporting Community Pharmacies with Implementation of a Web-Based Medication Management Application - Turner, Kea; Renfro, Chelsea; Ferreri, Stefanie; Roberts, Kim; Pfeiffenberger, Trista; Shea, Christopher M. (Applied Clinical Informatics, 2018)
Objective Community pharmacists' role in clinical care is expanding in the United States and information systems are needed that extend beyond a dispensing workflow. As pharmacies adopt new systems, implementation support will be needed. This study identifies the barriers and facilitators experienced by community pharmacies in implementing a Web-based medication management application and describes the implementation strategies used to support these pharmacies.Methods Semistructured interviews were conducted with 28 program and research staff that provides support to community pharmacies participating in a statewide pharmacy network. Interviews were recorded, transcribed verbatim, and analyzed for themes using the Expert Recommendations for Implementing Change (ERIC).Results Findings suggest that leadership support, clinical training, and computer literacy facilitated implementation, while lack of system integration, staff resistance to change, and provider reluctance to share data served as barriers. To overcome the barriers, implementation support was provided, such as assessing readiness for implementation, developing a standardized and interoperable care plan, and audit and feedback of documentation quality.Conclusion Participants used a wide array of strategies to support community pharmacies with implementation and tailored approaches to accommodate pharmacy-specific preferences. Most of the support was delivered preimplementation or in the early phase of implementation and by program or research staff rather than peer-to-peer. Implementing new pharmacy information system requires a significant amount of implementation support to help end-users learn about program features, how to integrate the software into workflow, and how to optimize the software to improve patient care. Future research should identify which implementation strategies are associated with program performance.
Keywords: community pharmacy; pharmacy information systems; implementation and deployment; medication management; clinical documentation; implementation science; medication management application; documentation